Documentação semântica no apoio à integração de dados e rastreabilidade - Arantes, Lucas de Oliveira (2010)
Documents are important mechanisms to register and disseminate knowledge and allow communication between human beings. Software Organizations use this mechanism to conduct projects. When these organizations reach a certain level of maturity they tend to use software document models in order to support the documentation process. Additionally, organizations count on processes and mechanisms to track the evolution of documents involved in a project. The amount of documents produced during a software project lifecycle can be considerably large. Despite the fact that version control systems support document centralization they are not capable of support information integration and visibility. Summing up, documents are treated as a set of characters tied with formatting styles because their primary goal is to be well rendered on a document authoring tool. In this context, adding domain ontology based metadata can help developing semantic documents, which, in turn, can help overcoming this scenario. Manual Semantic Annotation is notably dull and error prone. Combining document models semantic annotation is a viable option in order to achieve the annotation process automatization. Thus, uniting integration mechanisms provided by version control systems and software document models semantically annotated is a potential way of supporting information integration and, therefore, executing software projects. This work treats the use of software document models annotated semantically and version control mechanisms to track and register the evolution of a semantic document content (instantiated from a semantic model) and the provision of data visibility and integration services. In this sense, a Platform for Managing Semantic Documents is defined.